Zoysiagrass sod performance, rooting characteristics, and thatch accumulation among genotypes - Ojeokun, Olayemi Christiana (My University, 2024)
Zoysiagrass (Zoysia spp.) is valued for its adaptability, drought tolerance, and low input requirements, making it ideal for diverse landscapes, including golf courses and home lawns in the U.S. transition zone and southern regions. This thesis evaluates the performance, and resilience, of zoysiagrass under varying conditions, focusing on sod establishment, drought avoidance mechanisms, and thatch accumulation. Three studies were conducted to assess turfgrass adaptation and quality (i) the influence of aerification and grow-in treatments on sod performance, (ii) root traits for drought avoidance mechanisms, and (iii) thatch accumulation and genotype traits. The first study (Chapter 2) investigated three cultivars that were grown from sprigs under two nitrogen rates (1.6 lbs. or 3.6 lbs./1000 ft²/yr) and two mowing heights (0.75 in. or 1.5 in.). After harvest sod was installed at two Kansas locations (Olathe and Manhattan), on an aerified and nonaerified soil. After comparing the performance of the three cultivars, we found that aerification prior to sodding declined the NDVI of DALZ 1808 in both locations and the overall quality in Olathe. Meyer and Innovation NDVI and overall quality were not affected by aerification. In Olathe, sod grown under low mowing heights prior to harvest had 8.8% more root numbers than the higher mowing height. In Manhattan, Meyer zoysiagrass had a slightly longer root length than Innovation or DALZ 1808 within 9 days after sod was installed. Drought symptoms (visually on a 1 to 9 scale, 9 = no wilting, no stress) during the three weeks of dry-down showed that ‘Meyer’ had more significant drought symptoms (6.2) compared to Innovation (7.1) and DALZ 1808 (7.2) in Olathe, suggesting that cultivars respond differently to drought stress. The second study (Chapter 3) analyzed the rooting characteristics including rooting depth and shoot-to-root ratio (SRR) of 12 zoysiagrass genotypes in a greenhouse. The genotypes, grown in PVC tubes filled with calcined clay, were subjected to maximum root length evaluation at the end of the experiment and weekly ratings of shoot quality. Several additional rooting architecture traits in 10 cm depth zones were assessed using WinRHIZO software. The maximum root lengths were 53.5 cm (2023, Chisholm) and 61.5 cm (2024, DALZ 1311); all others were not significantly different in maximum root length except Zeon (2024) and KSUZ 1201 (2023, 2024). The highest root length among all genotypes was between 0 to 10 and 10 to 20 cm. As we evaluated deeper into the rootzone, cultivars that consistently showed lower root lengths, such as 20 to 30 cm, were DALZ 1702, KSUZ 1201 (2023), and Zeon (2024). Zeon consistently had high shoot quality, but KSUZ 1201 and DALZ 1702 had lower shoot quality (< 6 on a 1 to 9 scale), likely resulting in lower root development. The third study (Chapter 4) evaluated thatch accumulation and its possible influence on zoysiagrass performance across multiple environments as part of the National Turfgrass Evaluation Program (NTEP) and United States Golf Association (USGA) research trials in Kansas, Oklahoma, Indiana, Texas, and Florida. Only a few sites had differences among genotypes in thatch depth and mass. ‘Emerald’ accumulated the greatest thatch depth in Texas (NTEP trial), while DALZ 1311 had the lowest in Oklahoma (NTEP). Correlation of thatch depth was evaluated for ratings of genotypes’ traits; Thicker thatch depth was correlated with reduced turfgrass firmness in Texas (NTEP) and Citra (USGA) sites. Thatch depth was positively correlated with increased NDVI levels in Texas and Citra (NTEP) while it was negatively correlated with NDVI levels in Indiana (USGA). Increased thatch depth was positively correlated with increased tiller numbers in Oklahoma, Texas and Ft. Lauderdale. Overall, this thesis provides an understanding of the influence of different grow-in strategies on the performance of zoysiagrass genotypes, the adaptation of genotypes to specific locations based on their rooting abilities, and the effect of thicker thatch depth and higher thatch mass on turfgrass performance.
Keywords: Zoysiagrass; Sod establishment; Rooting characteristics; Thatch accumulation